STUDENTS’ WRITING ESSAY ABILITY OF “ILMU PERPUSTAKAAN ISLAM” - Elvina Gusman (Alfuad: Jurnal Sosial Keagamaan, 2018)
This research was conducted to see how the ability of students majoring in Islamic Library Science, Faculty of Islamic Law Adab and the Da'wah IAIN Batusangkar in writing discourse. In general, the components of writing discourse that are of concern are Organization, Content, Grammar and Sentence structure, Mechanics and Vocabulary. This research focuses on organization and grammar and sentence structure. This research uses descriptive method. The data of this study were taken from the test of the ability to write discourse by students of Islamic Library Science in the first year. Then, the data is analyzed using the qualitative method. The results of this study indicate that of 38 students majoring in Islamic Library Science, 20 students were able to write discourse while 18 students were only able to write a few sentences. Of the 20 discourses, 1 discourse has used writing components very well. 4 discourses are already using writing components well. 5 discourses are categorized as moderate. 10 discourses are categorized as lacking and there are no discourses categorized as very lacking in using writing components, especially organization and grammar and sentence structure.